2017
DOI: 10.1039/c7ob01656e
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged bioluminescence imaging in living cells and mice using novel pro-substrates forRenillaluciferase

Abstract: The prodrug or caged-luciferin strategy affords an excellent platform for persistent bioluminescence imaging. In the current work, we designed and synthesized ten novel pro-substrates for Renilla luciferase by introducing ester protecting groups of different sizes into the carbonyl group of the free luciferin 1. Taking advantage of intracellular esterases, lipases, and nucleophilic substances, the ester protecting groups were hydrolyzed, resulting in the release of a free luciferin and a bioluminescence signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The brightness and tissue penetration of the bioluminescent signal has limited its wide application in vivo. In previous studies 12,[21][22][23] , nearly all in vivo cell-tracking experiments with bioluminescence used a small animal (mouse or zebrafish, etc.) as research model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brightness and tissue penetration of the bioluminescent signal has limited its wide application in vivo. In previous studies 12,[21][22][23] , nearly all in vivo cell-tracking experiments with bioluminescence used a small animal (mouse or zebrafish, etc.) as research model.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing bioluminescence brightness intensity is a trend in the associated research. Yuan et al 21 designed and synthesized pro-substrates to enhance the improved light signal, and found that butyryloxymethyl luciferin 7 can serve as a promising long-term bioluminescence imaging probe. Gregor et al 12 reported the generation of an improved bacteria luciferase with an approximately 7-fold increased brightness.…”
Section: Discussionmentioning
confidence: 99%
“…The designed luminescent pairs provide more selections, and these luciferin analogs might be able to be biosynthesized in plant cells. Given that the potential cytotoxicity and growth inhibition to higher plants caused by bioluminescent systems, protecting groups were introduced into luciferin, which can decrease cytotoxicity and enhance the accumulation of luciferin (Yuan et al, 2017).…”
Section: Optimization Of “Planterns”mentioning
confidence: 99%
“…Instead, the effect of DMSO in the hydrolytic mechanism should be considered, as it is itself responsible for drastic changes compared to what has been observed in aqueous solutions (27). Yuan and coworkers (29) report an opposite hydrolytic trend of derivative 4a dissolved in water, which is necessarily related to solvent change. Literature suggests that organic carboxylic acids show an increasing value of pKa (as example, acetic acid from 4.76 to 12.3) when dissolved in DMSO (30), which means the protonated form of the acids is more stable in this solvent.…”
Section: Kinetic Studiesmentioning
confidence: 99%